Case report: Clinical and genetic characterization of a novel ALDH7A1 variant causing pyridoxine-dependent epilepsy, developmental delay, and intellectual disability in two siblings - Mustafa A. Salih; Albandary AlBakheet; Rawan Almass; Ahlam A. A. Hamed; Ali AlOdaib; Namik Kaya (Frontiers in Psychiatry)
BackgroundPathogenic variants in ALDH7A1 are associated with pyridoxine-dependent epilepsy (PDE), a rare autosomal recessive disorder characterized by epileptic seizures, unresponsiveness to standard antiseizure medications (ASM), and a response only to pyridoxine. Here, we report two patients (from a consanguineous family) with neonatal seizures and developmental delay.Case presentationPatient 1 (a 13-year-old girl) was born normally at term. Her pregnancy was complicated by antiphospholipid syndrome, and persistent vomiting was managed with several medications, including pyridoxine (40 mg daily). Seizures occurred 6 h after birth and did not respond to antiseizure medications. However, they ceased 2 days later when pyridoxine (40 mg daily) was administered. She continued her medications and had delayed early milestones. Phenobarbitone was discontinued at 18 months, and pyridoxine was increased to 100 mg daily at 8 years of age. She was able to join a regular school and performed well. Patient 2, a 12-year-old boy, was delivered normally at term. Seizures started 10 h after birth, and he immediately received 40 mg of pyridoxine. Seizures have been controlled since then, and he experienced delayed milestones. Pyridoxine was increased to 100 mg daily at 7 years of age. He is currently in fifth grade and has dyslexia. Whole exome sequencing (WES) revealed that both patients 1 and 2 harbor a novel homozygous missense variant in ALDH7A1 (NM_001202404: exon 12: c.1168G>C; (p.Gly390Arg)).ConclusionThe present study reports a novel ALDH7A1 variant causing PDE and highlights the associated developmental delay and intellectual disability, despite early seizure control treatment.